2006
DOI: 10.1021/bi0514109
|View full text |Cite
|
Sign up to set email alerts
|

Azotobacter vinelandiiVanadium Nitrogenase:  Formaldehyde Is a Product of Catalyzed HCN Reduction, and Excess Ammonia Arises Directly from Catalyzed Azide Reduction

Abstract: The nitrogenase-catalyzed reduction of both cyanide and azide results in the production of "excess NH 3 ", which is an amount of NH 3 over and above that expected to be formed from the wellrecognized reactions. Several suggestions have been made as to the possible sources of "excess NH 3 ", but previous attempts to characterize these reactions have met with either limited (or no) success or controversy. Because V-nitrogenase has a propensity to release partially reduced intermediates, e.g., N 2 H 4 during N 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 46 publications
0
41
0
1
Order By: Relevance
“…Here several accurate structural methods for small molecules converge in the determination of the proton in the α–hydroxy group of hydroxycarboxylates. Although there is a large gap between the coordination chemistry of mononuclear α–hydroxycarboxylato vanadium/molybdenum with the biological homocitrate system, and the vanadyl hydroxycarboxylates of citrate, malate or S -citramalate does not involve R -homocitrate, the present formation of unsymmetric mononuclear hydroxycarboxylato vanadyl compounds 1 ~ 6 could still be related to the coordination of homocitrato FeV-cofactor in nitrogenase [5, 49], that may show an unusual neutral α-hydroxy coordination in low oxidation state (+3 ~ +4) [50] as shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…Here several accurate structural methods for small molecules converge in the determination of the proton in the α–hydroxy group of hydroxycarboxylates. Although there is a large gap between the coordination chemistry of mononuclear α–hydroxycarboxylato vanadium/molybdenum with the biological homocitrate system, and the vanadyl hydroxycarboxylates of citrate, malate or S -citramalate does not involve R -homocitrate, the present formation of unsymmetric mononuclear hydroxycarboxylato vanadyl compounds 1 ~ 6 could still be related to the coordination of homocitrato FeV-cofactor in nitrogenase [5, 49], that may show an unusual neutral α-hydroxy coordination in low oxidation state (+3 ~ +4) [50] as shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of wild-type QueF complexed with substrate was determined using the molecular replacement Bayesian protocol in the program Phaser (16) and a search model generated from the structure of V. cholerae QueF (Protein Data Bank (PDB) ID 3BP1 (11)) by replacing nonhomologous residues with alanines. A solution with highest likelihood gain was obtained in the P3 2 21 space group. The partial model obtained in Phaser and describing the asymmetric unit was used for automatic tracing and refinement in the program Arp/Warp (17), which produced a significantly more complete model with a crystallographic R-factor of 0.35.…”
Section: Methodsmentioning
confidence: 99%
“…It was later shown that hydrogen cyanide (HCN) is the substrate, while CN − is the inhibitor [59]. The 2 e − /H + , 4 e − /H + , and 6 e − /H + reduction of HCN was observed with the production of methyleneimine (CH 2 =NH), methylamine (CH 3 NH 2 ), methane (CH 4 ), and ammonia (NH 3 ) as products for both the Mo- and V-nitrogenases [60,61]. The hydrolysis of unstable methyleneimine led to the production of formaldehyde and ammonia as the final products (Table 1).…”
Section: Early C-compounds and Nitrogenasementioning
confidence: 99%
“…The hydrolysis of unstable methyleneimine led to the production of formaldehyde and ammonia as the final products (Table 1). The further reduction of formaldehyde to methanol was not found [61]. However, very small amounts of C2 products, C 2 H 4 and C 2 H 6 , were observed, which might be derived from an insertion mechanism accounting for the isocyanide reduction and coupling [59,62].…”
Section: Early C-compounds and Nitrogenasementioning
confidence: 99%